2011
DOI: 10.1007/s10562-011-0654-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Activities of γ-Ga2O3–Al2O3 Catalysts for Methane-SCR of NO by Treatment with NH3

Abstract: The precursor particles for c-Ga 2 O 3 -Al 2 O 3 solid solutions were prepared by the coprecipitation method from aqueous solutions of Ga(NO 3 ) 3 and Al(NO 3 ) 3 with (NH 4 ) 2 CO 3 as a precipitant. The c-Ga 2 O 3 -Al 2 O 3 solid solutions were obtained by calcination of the precursor at 700°C. In this paper, the performance of the catalysts treated with NH 3 was investigated for the selective catalytic reduction (SCR) of NO with methane as a reducing agent, and it was found that c-Ga 2 O 3 -Al 2 O 3 catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The catalytic chemistry of γ-Al 2 O 3 has been widely investigated, and indeed its use as a catalyst support is commonplace . The solid solution γ-Ga 2 O 3 –γ-Al 2 O 3 has also been investigated for specific catalysis applications, and it is believed that preferential occupation of the tetrahedral sites by gallium leads to unique properties for the surface aluminum, such as in methane-selective catalytic reduction of NO, and in the dehydrogenation of propene. γ-Ga 2 O 3 has itself been studied for various applications in catalysis and compared with other Ga 2 O 3 polymorphs; for example, in the steam reforming of methanol and the photocatalytic degradation of volatile organics. , Recently Lueangchaichaweng et al have reported the use of gallium oxide nanorods, largely the γ polymorph, as highly effective catalysts for epoxidation reactions of alkenes . Interesting optical properties have also been a focus of recent attention for γ-Ga 2 O 3 : Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic chemistry of γ-Al 2 O 3 has been widely investigated, and indeed its use as a catalyst support is commonplace . The solid solution γ-Ga 2 O 3 –γ-Al 2 O 3 has also been investigated for specific catalysis applications, and it is believed that preferential occupation of the tetrahedral sites by gallium leads to unique properties for the surface aluminum, such as in methane-selective catalytic reduction of NO, and in the dehydrogenation of propene. γ-Ga 2 O 3 has itself been studied for various applications in catalysis and compared with other Ga 2 O 3 polymorphs; for example, in the steam reforming of methanol and the photocatalytic degradation of volatile organics. , Recently Lueangchaichaweng et al have reported the use of gallium oxide nanorods, largely the γ polymorph, as highly effective catalysts for epoxidation reactions of alkenes . Interesting optical properties have also been a focus of recent attention for γ-Ga 2 O 3 : Chen et al.…”
Section: Introductionmentioning
confidence: 99%